Control of soil N cycle processes by Pteridium aquilinum and Erica cinerea in heathlands along a pH gradient. Issue 9 (19th September 2018) - Bardon, Clément; Misery, Boris; Piola, Florence; Poly, Franck; Le Roux, Xavier
Abstract: Nitrate is a limiting resource in heathland acid soils. Nitrate levels increase in heathland soils after Pteridium aquilinum invasions, and this species is assumed to biologically control nitrogen cycle processes, thus increasing nitrate availability. We compared how P. aquilinum (bracken) and Erica cinerea (bell heather) modify processes driving nitrate availability along a soil pH gradient in a Natura 2000 reserve facing bracken invasion. Soil nitrate and ammonium concentrations, substrate‐induced respiration (SIR), denitrification and nitrification enzyme activities (DEA and NEA, respectively), root procyanidin concentrations, and denitrification inhibition by procyanidins were measured on five sites under P. aquilinum and E. cinerea stands. NEA and nitrate levels were higher, and ammonium levels and SIR lower, for P. aquilinum in the most acid soils. Procyanidins from both species induced the same level of denitrification inhibition, soil nitrate being correlated with root procyanidin concentration for both species. Soil nitrate correlated with NEA only for P. aquilinum . Our results show that both species increased procyanidin production in the most acid soils, thereby reducing denitrification and decreasing nitrate loss, this process being more efficient for E. cinerea . However, P. aquilinum additionally increased nitrification, and this double control on nitrification and denitrification was very efficient to increase soil nitrate availability in the most acid soils. This may participate to the success of P. aquilinum invasions in heathlands. This shows that approaches for bracken control in heathlands should better account for belowground processes and, more generally, that biological denitrification inhibition by plants may be a widespread phenomenon influencing soil N dynamics in N‐poor environments.